Standards and Criteria* - Gene V. Glass (The Evaluation Center at Western Michigan University, 2011)
Originally published as Paper #10, Occasional Paper Series, December, 1977 * This monograph was prepared under a grant from the Carnegie Corporation. Mary Lee Smith contributed at every stage of the preparation of this monograph; reading the literature, developing the ideas, outlining and editing the final product. Nancy W. Burton helped in developing the topic. Laura A. Driscoll and Gregory C. Camilli deserve thanks for assistance in literature search and data analysis. Conversation among Glass, Smith, Burton, and Robert Glaser on a day in June 1976 got things started; we are much indebted to Glaser for helping set things off in a direction that now pleases us.